2006
DOI: 10.1016/j.jacc.2006.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Blocker Use and Outcomes Among Hospitalized Heart Failure Patients

Abstract: Beta-blocker therapy before and during hospitalization for HF is associated with improved outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 13 publications
4
51
0
3
Order By: Relevance
“…Future studies are need to investigate whether cardiac resynchronization therapy during hospitalization and the prescription of beta-blockers at the time of hospital discharge might favorably reduce post-discharge mortality compared to patients without HF hospitalizations. [36][37][38] A recent post hoc analysis of CHARM database demonstrated that post-baseline "discharge for first hospitalization for HF" was independently associated with increased mortality (HR 3.15; 95% CI, 2.83-3.50; p<0.0001). 39 This is very similar to the association observed in the current study (HR, 2.49, 95%CI, 1.97-3.13; p<0.0001) and provide cumulative evidence of the deleterious effect of HF hospitalization on subsequent survival in chronic HF.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are need to investigate whether cardiac resynchronization therapy during hospitalization and the prescription of beta-blockers at the time of hospital discharge might favorably reduce post-discharge mortality compared to patients without HF hospitalizations. [36][37][38] A recent post hoc analysis of CHARM database demonstrated that post-baseline "discharge for first hospitalization for HF" was independently associated with increased mortality (HR 3.15; 95% CI, 2.83-3.50; p<0.0001). 39 This is very similar to the association observed in the current study (HR, 2.49, 95%CI, 1.97-3.13; p<0.0001) and provide cumulative evidence of the deleterious effect of HF hospitalization on subsequent survival in chronic HF.…”
Section: Discussionmentioning
confidence: 99%
“…17 Other studies have also reported pretreatment BP as a predictor of h-blocker tolerability in patients with HF. 7,[18][19][20] Although the tolerability of nebivolol (as with many drug treatments) may be dependent on a more favorable clinical profile, it is also possible that physicians were more likely to withhold the treatment if side effects occurred in bsickerQ patients. Our data show that given the markedly increased risk on all outcomes in these patients, increased efforts should be made to initiate and maintain h-blocker therapy wherever possible in elderly patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…Continuation of β‐blocker therapy at the time of hospital discharge has been shown to reduce both readmission and mortality rates after ADHF admissions 10, 11, 12. The impact of continuing or discontinuing ACEi/ARB after ADHF hospitalization has not been as well studied.…”
Section: Introductionmentioning
confidence: 99%